Growth in transport sector CO2 emissions in Tunisia: an analysis using a bounds testing approach. (2018) - Abbes, Souhir; Bulteau, Julie
This paper analyses the dynamic impacts of GDP growth, motorisation rate, transport pollution coefficient and energy intensity, on CO2 emissions from the transport sector in Tunisia. Empirical results from the ARDL approach show that over the 1971-2014 period, energy intensity and pollution coefficient were the most significant variables. The elasticities of motorisation rate to CO2 emissions were also significant and had the expected sign. These results not only contribute to advancing the existing literature but also provide important policy recommendations: to control transport emissions, policy-makers should invest in public transportation and reinforce the legislation on environmental standards of vehicles. Finally, the statistically insignificant effects of per capita GDP on transport carbon emissions in the long run suggest that it is possible to control these emissions without disrupting economic growth. This can be achieved by developing short sea shipping between the biggest cities to reduce road congestion and carbon emissions.